The Effects of Leadership and Commitment on the Job Performance of Lecturers at University - Jalaluddin Jalaluddin; Munawar Munawar; Azwir Azwir (STAI Hubbulwathan Duri, 2021)
The purpose of this study is to identify the effects of leadership style and commitment of the university leader on the performance of Serambi Mekkah University’s lecturers. A survey was used as the data collection technique, while path analysis was used as the testing technique. Likert-scale questionnaires with closed-ended questions regarding the effects of leadership and organizational commitment on the lecturers’ performance were employed. The questionnaires had an interval scale and an answer score on each question. It also had five different choices on a continuum line. The population of this research was all lecturers of Serambi Mekkah University, namely 270 lecturers in total, whereas the research sample was 122 lecturers. Data analysis was carried out in two stages, namely descriptive and inferential, using Microsoft Excel 2007. The results showed that there is a positive correlation between leadership (X1) and commitment (X2) on the performance of Serambi Mekkah University’s lecturers (Y). Based on the findings, it can be concluded that leadership and commitment significantly affect the performance of Serambi Mekkah University’s lecturers.